Culture in Translation and Interpreting - Meldia, Putri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This paper is aimed at explaining the concept of translating and interpreting a text or speech while paying attention to the target language's culture. There are several errors that often occur in translating and interpreting a text; the first is that there are still many translators who make mistakes that they consider normal, but have a big impact on the results of the translation which are not in accordance with the intent of the source language, namely forgetting that there is a culture that develops in writing, the second translator is still translating a text word by word, the three translators forgot the communication norms that developed in the target language. The data were collected through finding relevant reference Materials for a literature review include electronic books, journals, articles, and other sources of information. The literature review, as a tool for data collection, entails activities such as identifying, documenting, comprehension, implying, and transmitting data. Data collection is, throughout fact, how the literature review process is carried out,Â This paper used a literature review approach. To define the study of the notion of translation and interpretation that takes into account the target language's cultural features while keeping communicative norms in mind and produces meaning-based translation. The result of this study was applying meaning base translation and the cultural aspects in translation and interpretation by considering the communicative norms in the target language.Artikel ini bertujuan untuk menjelaskan bagaimana konsep menerjemahkan dan menafsirkan sebuah teks dalam bentuk tulisan atau pidato dalam bentuk lisan dengan memperhatikan unsure budaya yang berkembang dalam bahasa target. Ada beberapa kesalahan yang sering terjadi dalam menerjemahkan dan menafsirkan sebuah teks; yang pertama masih banyak penerjemah yang melakukan kesalahan yang mereka anggap biasa, namun hal tersebut berdampak besar terhadap hasil terjemahan yang tidak sesuai dengan maksud bahasa sumber yakninya melupakan satu hal yang sangat penting yaitu berbabsiskanÂ budaya yang berkembang secara tertulis, kedua penerjemah masih menerjemahkan teks dengan menggunakan metode mengartikan kata per kata, ketiga penerjemah melupakan bahwa dalam menerjemah harus ada communicative normsÂ (norma-norma yang berlaku) dalam bahasa target. Teknik pengumpulan data dilakukan peneliti dengan megumpulkan beberapa e-book, jurnal, artikel, dan sumber lain yang terkait sebagi sumber data pada penelitian ini. Tinjauan pustaka, sebagai alat untuk pengumpulan data, dengan cara mengidentifikasi, mendokumentasikan, memahami, menyiratkan, dan mentransmisikan data. Artikel ini menggunakan pendekatan tinjauan pustaka. Menjelaskan konsep mengenai Transaltion dan interpretation yang mempertimbangkan ciri-ciri budaya bahasa target serta tetap memperhatikan norma-norma komunikatif yang berkembang, kemudian menghasilkan terjemahan yang berlandaskan makna. Hasil dari penelitian ini adalah penerapan pendekatan budaya dalam penerjemahan dan interpretasi dengan memperhatikan norma-norma komunikatif yang berlaku dan berkembang dalam bahasa target.